Aluminum alloy surface defect repairing method and application thereof
By reacting magnesium oxide powder and aluminum magnesium carbonate powder with carbon dioxide to form a dense film layer, the surface defects caused by wear and corrosion of aluminum alloy rotors are solved, and efficient and low-cost surface repair is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411698154.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In a high vacuum environment, surface defects of aluminum alloy rotors are caused by wear and corrosion, which affects their normal operation. The existing repair technology is costly and inefficient, making it difficult to apply on a large scale on an industrial basis.
The surface of the aluminum alloy is repaired by a composition of magnesium oxide powder and aluminium magnesium carbonate powder. The surface strength and corrosion resistance are improved by reacting with carbon dioxide. The reaction conditions are adjusted to give priority. Generate films of different compounds to ensure repair results.
It realizes the formation of a dense film layer with good adhesion on the surface of aluminum alloy, extends the rotor life, reduces repair costs, improves production efficiency, and is suitable for large-scale industrial production.
Smart Images

Figure CN119177439A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy surface repair, and in particular to a method for repairing aluminum alloy surface defects and an application thereof. Background Art
[0002] As we all know, high vacuum chambers are required in chip and photovoltaic process technology, laser plasma devices, etc. Vacuum obtaining equipment such as molecular pumps with turbine blade rotors need to rotate tens of thousands of times per minute to produce the exhaust effect of gas molecules in the molecular flow area. In recent years, with the improvement of performance requirements of semiconductor and photovoltaic materials, the vacuum degree required for vacuum chambers has become higher and higher. At the same time, organic compounds in the process are highly corrosive, and silicon-containing dust will be generated in the etching process. These will accelerate the wear and corrosion of the rotor, causing defects on the rotor surface and affecting the subsequent normal operation of the rotor.
[0003] Aluminum alloy has the characteristics of light weight, good mechanical properties and corrosion resistance, making it an ideal choice for rotors. In view of this, how to repair aluminum alloy surface defects and extend the life of aluminum alloy rotors has become an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present invention is to provide a method for repairing aluminum alloy surface defects and its application, which can repair aluminum alloy surface defects and, when applied to aluminum alloy rotor repair, can maintain rotor balance and ensure normal operation of the rotor.
[0005] The present invention is achieved in that: In a first aspect, an embodiment of the present application provides a composition for repairing surface defects of aluminum alloys, comprising magnesium oxide powder and aluminum carbonate magnesium powder.
[0006] When aluminum alloy parts are used for a long time, defects will appear on the surface, affecting the normal operation of the aluminum alloy parts. For example, the rotor made of aluminum alloy is subjected to friction and corrosion during long-term operation, causing the surface oxidation protection layer to be destroyed and become loose and porous.
[0007] By using the aluminum alloy surface defect repairing composition in the embodiment of the present application to repair the surface of an aluminum alloy part, a densified film layer with good strength and toughness inlaid in rods and lamellar shapes can be generated at the defect site, and the film layer has good adhesion to the matrix alloy. At the same time, if the alloy part is a rotor, the impact on the rotor balance is small, which is beneficial to ensure the normal operation of the rotor.
[0008] The composition in the embodiment of the present application can be used to perform surface repair on aluminum alloys, wherein the aluminum alloy can be a 6 series aluminum alloy such as 6061, or other aluminum alloys.
[0009] In an optional embodiment, the mass ratio of the magnesium oxide powder to the aluminum carbonate powder is 1:(1-3).
[0010] Under this condition, when the magnesium oxide and aluminum magnesium carbonate powder are used to repair the aluminum alloy parts, the reaction advantage of magnesium can be guaranteed, and a magnesium-containing compound film layer is first generated at the defect, and then an aluminum-containing compound film layer is generated, wherein the first-generated magnesium-containing compound film layer can fill the defect, and the later-generated aluminum-containing compound film layer covers the magnesium-containing compound, and the adhesion between the aluminum-containing compound and the oxide film on the surface of the aluminum alloy is greater, which is beneficial to reduce the occurrence of cracks at the repaired aluminum alloy parts.
[0011] In an optional embodiment, the magnesium oxide powder is nano magnesium oxide.
[0012] Nano magnesium oxide has a smaller particle size, which is beneficial to promote the reaction of magnesium oxide to form a magnesium compound film during the repair process.
[0013] In a second aspect, an embodiment of the present application provides a method for repairing aluminum alloy surface defects, comprising: Pretreatment: take the aluminum alloy after surface cleaning, and cover the defects of the aluminum alloy with the composition described in any one of the above embodiments; Surface reaction, placing the aluminum alloy in a reaction chamber, introducing carbon dioxide into the reaction chamber, and forming a first film layer at defects of the aluminum alloy; curing, after the surface reaction is completed, continuing to introduce carbon dioxide into the reaction chamber to form a second film layer on the first film layer; After the curing step is completed, the aluminum alloy is cooled and the composition attached to the surface is removed.
[0014] In the embodiment of the present application, when repairing the surface defects of the aluminum alloy, first, the composition for repairing the surface defects of the aluminum alloy is covered on the defect to be repaired. Specifically, the composition is in powder form and can be directly sprinkled on the defect of the aluminum alloy when covering. After the reaction is completed, the excess composition attached to the surface can be removed; then a surface reaction is carried out, the composition reacts with carbon dioxide to form a first film layer, i.e., a magnesium compound-containing film layer, at the defect; finally, maintenance is carried out, at which time the composition continues to react with carbon dioxide to form a second film layer, i.e., an aluminum compound-containing film layer, at the defect, completing the repair of the aluminum alloy surface, and at this time, the excess composition on the surface can be removed.
[0015] It should be noted that the magnesium-containing compound film layer described in the embodiment of the present application mainly includes magnesium-containing compounds and also contains a small amount of aluminum-containing compounds; the aluminum-containing compound film layer mainly includes aluminum-containing compounds and also contains a small amount of magnesium-containing compounds; that is, compared with the first film layer and the second film layer, the mass fraction of magnesium-containing compounds in the first film layer is higher than that in the second film layer, and the mass fraction of aluminum-containing compounds in the second film layer is higher than that in the first film layer.
[0016] This method uses carbon dioxide and magnesium salt as intermediates to repair aluminum alloy surface defects, providing new ideas and technical references for aluminum alloy surface protection treatment technology; in addition, the method has a simple implementation process, low cost, environmental friendliness, high production efficiency, and is conducive to large-scale industrial production.
[0017] In an optional embodiment, in the surface reaction step, the flow rate of carbon dioxide is 1 L / h-3 L / h, the temperature in the reaction chamber is 80°C-100°C, the gauge pressure in the reaction chamber is 1 Bar-1.5 Bar, and the reaction time is 5h-10h.
[0018] Under these conditions, the composition can react with carbon dioxide to preferentially form a film layer containing a magnesium compound.
[0019] In an optional embodiment, in the curing step, the flow rate of carbon dioxide is less than 0.5 L / h, and the temperature in the reaction chamber is 70° C.-100° C.
[0020] Under these conditions, the composition can react with carbon dioxide to preferentially form a film layer containing an aluminum compound.
[0021] In the embodiment of the present application, in the surface reaction and oxidation steps, the priority of the formation of aluminum-containing compounds and magnesium-containing compounds is adjusted mainly by adjusting the reaction pressure and the carbon dioxide flow rate. High pressure and high carbon dioxide flow rate are conducive to the formation of magnesium-containing compounds; atmospheric pressure and low carbon dioxide flow rate are conducive to the formation of aluminum-containing compounds.
[0022] It should be noted that by controlling the various parameters in the curing and surface reaction, the reaction rate can be regulated, and then the generation rate of the first film layer and the second film layer can be adjusted, which will affect the uniformity of the first film layer and the second film layer to a certain extent; in addition, since water will react with the composition, affecting the composition of the first film layer and the second film layer, and then affecting the repair effect, during the surface reaction and curing steps, the introduction of water into the reaction environment should be avoided as much as possible, and the carbon dioxide introduced should be dried carbon dioxide.
[0023] In an optional embodiment, during the curing step, the temperature fluctuation in the reaction chamber is less than 5° C. / h.
[0024] The formation of the aluminum oxide-containing film layer is relatively sensitive to temperature. Therefore, the temperature fluctuation during the curing step should not be too drastic, otherwise it will affect the uniformity of the second film layer and thus affect the repair effect.
[0025] In an optional embodiment, in the surface reaction step, the temperature of introducing carbon dioxide is 90°C-110°C; And / or, in the curing step, the temperature of the introduced carbon dioxide is 18°C-25°C.
[0026] In the surface reaction step, the carbon dioxide gas flow rate is relatively large. In order to reduce the impact of carbon dioxide on the reaction temperature, carbon dioxide at a higher temperature can be introduced. In the curing step, the carbon dioxide gas flow rate is small and has little impact on the curing temperature. Carbon dioxide at room temperature can be introduced to simplify the device.
[0027] In an optional embodiment, before the pre-treatment step, the aluminum alloy is also included in cleaning, and the cleaning step includes: placing the aluminum alloy to be repaired in anhydrous acetone and performing a first ultrasonic treatment, immersion, a second ultrasonic treatment and drying in sequence; the first ultrasonic treatment time is 50min-70min, the ultrasonic frequency is 100KHz-130KHz, and the ultrasonic power density is 15W / L-20W / L; the immersion time is 30min-40min; and the second ultrasonic treatment time is 10min-20min.
[0028] Immersing between two ultrasonic treatments can achieve better cleaning effect on the aluminum alloy surface.
[0029] In a third aspect, an embodiment of the present application provides an aluminum alloy repaired using the method described in any of the aforementioned embodiments.
[0030] The first film layer and the second film layer formed on the surface of the aluminum alloy can protect the aluminum alloy and improve the corrosion resistance of the aluminum alloy.
[0031] In a fourth aspect, an embodiment of the present application provides a rotor made of aluminum alloy, which is repaired using the method described in any of the aforementioned embodiments, wherein the total thickness of the first film layer and the second film layer is 5 μm-10 μm.
[0032] Specifically, the aforementioned method for repairing aluminum alloy surface defects can be used to repair the rotor after the first anodization, so as to obtain the rotor made of aluminum alloy in the embodiment of the present application. A reasonable film layer thickness is beneficial for repairing defects without affecting the balance of the rotor.
[0033] The present invention has the following beneficial effects: By using the aluminum alloy surface defect repairing composition in the embodiment of the present application to repair the surface of an aluminum alloy part, a densified film layer with good strength and toughness inlaid in rods and lamellar shapes can be generated at the defect site, and the film layer has good adhesion to the matrix alloy. At the same time, if the alloy part is a rotor, the impact on the rotor balance is small, which is beneficial to ensure the normal operation of the rotor. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a schematic diagram of the structure of the repair device used in Example 1; Figure 2 This is the SEM image of the aluminum alloy rotor after pretreatment in Example 1 (typical pore diameters measured in the fields of view of A 50 μm, B 10 μm, and C 10 μm); Figure 3 This is the SEM image of the aluminum alloy rotor after repair in Example 1 (typical pore diameters measured under the fields of view of A 50μm, B 10μm and C 4μm); Figure 4 This is a longitudinal SEM image of the aluminum alloy rotor after repair in Example 1; Figure 5 This is the SEM image of the longitudinal section of the repaired aluminum alloy rotor in Comparative Example 1 after continuous operation for 168 hours at the limiting speed.
[0036] Diagram: 1-reaction chamber; 2-reaction furnace; 3-aluminum alloy rotor; 4-heater; 5-probe; 6-temperature control system; 7-pressure gauge. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0038] An embodiment of the present application provides a composition for repairing surface defects of aluminum alloys, comprising magnesium oxide powder and aluminum carbonate powder.
[0039] By using the aluminum alloy surface defect repairing composition in the embodiment of the present application to repair the surface of an aluminum alloy part, a densified film layer with good strength and toughness inlaid in rods and lamellar shapes can be generated at the defect site, and the film layer has good adhesion to the matrix alloy. At the same time, if the alloy part is a rotor, the impact on the rotor balance is small, which is beneficial to ensure the normal operation of the rotor.
[0040] In an optional embodiment, the mass ratio of the magnesium oxide powder to the hydrotalcite powder is 1:(1-3), specifically, it can be 1:1, 1:2, 1:3 or any value in between 1:(1-3).
[0041] The mass ratio of magnesium oxide to aluminum carbonate powder is in the range of 1: (1-3), which is beneficial to ensure the priority generation of magnesium-containing compounds. However, if the proportion of magnesium oxide in the composition is too high, it will be more difficult to generate the required aluminum-containing oxide during the curing step, and cracks will be easily generated at the repaired area.
[0042] In an optional embodiment, the magnesium oxide powder is nano magnesium oxide.
[0043] Nano magnesium oxide has a smaller particle size, which is beneficial to promote the reaction of magnesium oxide to form a magnesium compound film during the repair process.
[0044] The present application also provides a method for repairing aluminum alloy surface defects, comprising: Pretreatment: take the aluminum alloy after surface cleaning, and cover the defects of the aluminum alloy with the composition described in any one of the above embodiments; Surface reaction, placing the aluminum alloy in a reaction chamber 1, introducing carbon dioxide into the reaction chamber 1, and forming a first film layer at defects of the aluminum alloy; Maintenance: After the surface reaction is completed, continue to introduce carbon dioxide into the reaction chamber 1 to form a second film layer on the first film layer; After the curing step is completed, the aluminum alloy is cooled and the composition attached to the surface is removed.
[0045] In the embodiment of the present application, when repairing the surface defects of the aluminum alloy, first, the composition for repairing the surface defects of the aluminum alloy is covered on the defect to be repaired. Specifically, the composition is in powder form and can be directly sprinkled on the defect of the aluminum alloy when covering. After the reaction is completed, the excess composition attached to the surface can be removed; then a surface reaction is carried out, the composition reacts with carbon dioxide to form a first film layer, i.e., a magnesium compound-containing film layer, at the defect; finally, maintenance is carried out, at which time the composition continues to react with carbon dioxide to form a second film layer, i.e., an aluminum compound-containing film layer, at the defect, completing the repair of the aluminum alloy surface, and at this time, the excess composition on the surface can be removed.
[0046] It should be noted that the equipment used in the surface reaction and curing steps should include a reaction furnace 2 containing a reaction chamber 1, and the reaction furnace 2 is provided with a heater 4 for heating the reaction chamber 1 and a probe 5 for monitoring the temperature in the reaction chamber 1, and the probe 5 and the heater 4 are both connected to a temperature control system 6, and the temperature control system 6 controls the power and switch of the heater 4 according to the monitoring data of the probe 5; in order to regulate the pressure in the reaction chamber 1, a pressure gauge 7 is also provided; in order to facilitate the entry and exit of carbon dioxide into and out of the reaction chamber 1, the reaction furnace 2 is also provided with an air inlet and an air outlet, and the specific structure can be referred to Figure 1 .
[0047] In an optional embodiment, in the surface reaction step, the flow rate of carbon dioxide is 1L / h-3L / h, specifically 1L / h, 2L / h, 3L / h or any value between 1L / h and 3L / h; the temperature in the reaction chamber 1 is 80°C-100°C, specifically 80°C, 90°C, 100°C or any value between 80°C and 100°C; the gauge pressure in the reaction chamber 1 is 1Bar-1.5Bar, specifically 1Bar, 1.1Bar, 1.2Bar, 1.3Bar, 1.4Bar, 1.5Bar or any value between 1Bar and 1.5Bar; the reaction time is 5h-10h, specifically 5h, 6h, 7h, 8h, 9h, 10h or any value between 5h and 10h.
[0048] Under this condition, the composition can react with carbon dioxide to preferentially generate a magnesium compound-containing film layer. In an optional embodiment, in the curing step, the flow rate of carbon dioxide is less than 0.5 L / h, specifically 0.1 L / h, 0.2 L / h, 0.3 L / h, 0.4 L / h, 0.5 L / h or any value less than 0.5 L / h; the temperature in the reaction chamber 1 is 70°C-100°C, specifically 70°C, 80°C, 90°C, 100°C or any value between 70°C-100°C.
[0049] Under these conditions, the composition can react with carbon dioxide to preferentially form a film layer containing an aluminum compound.
[0050] In an optional embodiment, during the curing step, the temperature fluctuation in the reaction chamber 1 is less than 5°C / h, specifically, it can be 1°C / h, 2°C / h, 3°C / h, 4°C / h, 5°C / h or any value less than 0.5°C / h. If the temperature fluctuation is too large, the uniformity of the second film layer will be reduced.
[0051] In an optional embodiment, in the surface reaction step, the temperature of the carbon dioxide introduction is 90°C-110°C, specifically 90°C, 100°C, 110°C or any value between 90°C and 110°C, which is beneficial to reduce the impact of the introduction of carbon dioxide on the reaction temperature.
[0052] In an optional embodiment, in the curing step, the temperature of the carbon dioxide introduced is 18°C-25°C, specifically 15°C, 180°C, 21°C, 25°C or any value between 18°C and 25°C. By introducing gas at room temperature, the waste heat step of the carbon dioxide can be reduced, which is conducive to simplifying the process and equipment.
[0053] In an optional embodiment, before the pre-treatment step, the aluminum alloy is also included in cleaning, and the cleaning step includes: placing the aluminum alloy to be repaired in anhydrous acetone and performing a first ultrasonic treatment, immersion, a second ultrasonic treatment and drying in sequence; the first ultrasonic treatment time is 50min-70min, the ultrasonic frequency is 100KHz-130KHz, and the ultrasonic power density is 15W / L-20W / L; the immersion time is 30min-40min; and the second ultrasonic treatment time is 10min-20min.
[0054] Immersing between two ultrasonic treatments can achieve better cleaning effect on the aluminum alloy surface.
[0055] The embodiments of the present application also provide an aluminum alloy which is repaired by the method described in any of the aforementioned embodiments and has good corrosion resistance and mechanical properties.
[0056] An embodiment of the present application also provides a rotor made of aluminum alloy, which is repaired by the method described in any of the aforementioned embodiments, wherein the total thickness of the first film layer and the second film layer is 5μm-10μm, specifically 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any value between 5μm and 10μm. If the total thickness is too high, it may affect the balance of the rotor; if the total thickness is too low, the corrosion resistance and mechanical properties are not significantly improved, and the probability of cracks in the rotor after long-term operation will increase.
[0057] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0058] Example 1 This embodiment provides a method for repairing an aluminum alloy rotor 3. The structure of the equipment used is as follows: Figure 1 As shown, the specific steps include: 1. Pretreatment: Place the rotor to be repaired in anhydrous acetone for the first ultrasonic treatment for 60 minutes, with an ultrasonic frequency of 110KHz and a power density of 18W / L. Then immerse it for 35 minutes and then ultrasonically clean it for 15 minutes. Then take the rotor out of the acetone, dry it with flowing air at room temperature, and perform SEM testing. The results are as follows: Figure 2 shown.
[0059] 2. Composition coating: A mixture of nano-magnesium oxide and hydrotalcite powder is coated on the surface of the aluminum alloy rotor 3, wherein the mass ratio of nano-magnesium oxide to hydrotalcite is 1:2.
[0060] 3. Surface reaction: The aluminum alloy rotor 3 is placed in the reaction chamber 1, and 100°C dry carbon dioxide gas is introduced. The surface pressure in the reaction chamber 1 is 1.3 Bar, the carbon dioxide flow rate is 2 L / h, the temperature in the reaction chamber 1 is 90°C, and the reaction time is 8 hours.
[0061] 4. Insulation and maintenance: Introduce carbon dioxide gas at room temperature, maintain the temperature of reaction chamber 1 at 85°C, with a temperature fluctuation of less than 5°C / h, and keep warm for 5 hours under atmospheric pressure. The flow rate of carbon dioxide gas is 0.2L / h.
[0062] 5. Post-processing: The aluminum alloy rotor 3 is cooled to room temperature in the furnace, and the excess powder on the surface is removed to obtain an aluminum alloy rotor 3 with a total thickness of the first film layer and the second film layer of 8 μm. SEM test is performed, and the results are as follows: Figure 3 shown.
[0063] from Figure 2 and Figure 3 By comparison, it can be seen that before repair, the pore density was about 0.4411 mm 2 / cm 2 The typical pore diameter is 3.334 μm; the pore density after repair is about 0.0615 mm 2 / cm 2 The typical pore diameter is 1.944 μm, indicating that the defects have been repaired. Figure 4 The middle is a cross-sectional view of the repaired aluminum alloy rotor 3, and it can be seen that there is a scaly layer on the surface of the repaired position of the aluminum alloy rotor 3. The repaired aluminum alloy rotor 3 of this embodiment was continuously operated at the limit speed for 168 hours, and no deep cracks and surface tears were found after longitudinal section SEM observation.
[0064] Example 2 This embodiment provides a method for repairing an aluminum alloy rotor 3 , which is different from Embodiment 1 only in that the mass ratio of nano-magnesium oxide to aluminum carbonate in the composition is increased to 1:1.
[0065] Example 3 This embodiment provides a method for repairing an aluminum alloy rotor 3 , which is different from Embodiment 1 only in that the mass ratio of nano-magnesium oxide to hydrotalcite in the composition is reduced to 1:3.
[0066] Example 4 This embodiment provides a method for repairing an aluminum alloy rotor 3, which specifically includes the following steps: 1. Pretreatment: Place the rotor to be repaired in anhydrous acetone for the first ultrasonic treatment for 60 minutes, with an ultrasonic frequency of 110KHz and a power density of 18W / L. Then immerse it for 35 minutes and then ultrasonically clean it for 15 minutes. Then take the rotor out of the acetone and blow it dry with flowing air at room temperature.
[0067] 2. Composition coating: A mixture of nano-magnesium oxide and hydrotalcite powder is coated on the surface of the aluminum alloy rotor 3, wherein the mass ratio of nano-magnesium oxide to hydrotalcite is 1:2.
[0068] 3. Surface reaction: The aluminum alloy rotor 3 is placed in the reaction chamber 1, and 100°C dry carbon dioxide gas is introduced. The surface pressure in the reaction chamber 1 is 1 Bar, the carbon dioxide flow rate is 1 L / h, the temperature in the reaction chamber 1 is 80°C, and the reaction time is 10 hours.
[0069] 4. Insulation and maintenance: introduce carbon dioxide gas at room temperature, maintain the temperature of reaction chamber 1 at 100°C, with a temperature fluctuation of less than 5°C / h, and keep warm for 4 hours. The flow rate of carbon dioxide gas is 0.1L / h.
[0070] 5. Post-processing: The aluminum alloy rotor 3 is cooled to room temperature in the furnace, and excess powder on the surface is removed to obtain an aluminum alloy rotor 3 with a total thickness of 4 μm for the first film layer and the second film layer.
[0071] Example 5 1. Pretreatment: Place the rotor to be repaired in anhydrous acetone for the first ultrasonic treatment for 60 minutes, with an ultrasonic frequency of 110KHz and a power density of 18W / L. Then immerse it for 35 minutes and then ultrasonically clean it for 15 minutes. Then take the rotor out of the acetone and blow it dry with flowing air at room temperature.
[0072] 2. Composition coating: A mixture of nano-magnesium oxide and hydrotalcite powder is coated on the surface of the aluminum alloy rotor 3, wherein the mass ratio of nano-magnesium oxide to hydrotalcite is 1:2.
[0073] 3. Surface reaction: The aluminum alloy rotor 3 is placed in the reaction chamber 1, and 100°C dry carbon dioxide gas is introduced. The surface pressure in the reaction chamber 1 is 1.5 Bar, the carbon dioxide flow rate is 3 L / h, the temperature in the reaction chamber 1 is 100°C, and the reaction time is 5 hours.
[0074] 4. Insulation and maintenance: Introduce carbon dioxide gas at room temperature, maintain the temperature of reaction chamber 1 at 70°C, with a temperature fluctuation of less than 5°C / h, and keep warm for 6 hours. The flow rate of carbon dioxide gas is 0.5L / h.
[0075] 5. Post-processing: The aluminum alloy rotor 3 is cooled to room temperature in the furnace, and excess powder on the surface is removed to obtain an aluminum alloy rotor 3 with a total thickness of 6 μm for the first film layer and the second film layer.
[0076] Comparative Example 1 This comparative example provides a method for repairing an aluminum alloy rotor 3, which differs from Example 1 only in that the surface reaction time is extended to 13 hours, and post-treatment is performed directly without performing a curing step.
[0077] The aluminum alloy rotor 3 after pretreatment and posttreatment was continuously operated at the limit speed for 168 hours. After longitudinal section, SEM observation revealed deep cracks and surface tears (such as Figure 5 The red arrow indicates the location).
[0078] Comparative Example 2 This comparative example provides a method for repairing an aluminum alloy rotor 3, which is different from Example 1 only in that after the composition is coated, thermal insulation curing is directly performed without surface reaction, and the thermal insulation curing time is extended to 13 hours.
[0079] 3. Aluminum alloy rotor after pretreatment and post-treatment.
[0080] The aluminum alloy specimens were repaired by the same method as in the above embodiments and comparative examples, and the repaired aluminum alloy specimens were subjected to a corrosion resistance test. The test method was as follows: a blank sample and an aluminum alloy specimen (with the same specifications and dimensions as the blank sample) repaired by the same method as in the above embodiments and comparative examples were placed in 50 ml of a 30% nitric acid solution, respectively, and the dissolution time of each specimen was tested. The test results are shown in Table 1.
[0081] The surface of a defect-free aluminum alloy sample with a size of 10 mm×15 mm×3 mm was subjected to micro-arc oxidation and sealed with a nickel-based sealant at medium temperature as a blank sample, wherein the steps and parameters of micro-arc oxidation and nickel-based sealant at medium temperature include: Preparation of electrolyte: NaOH and phytic acid were added to deionized water to prepare an electrolyte with a NaOH concentration of 6 g / L and a phytic acid concentration of 12 g / L.
[0082] Preparation of blocking solution: The mass ratio of commercially available nickel-based metal sealer (YM-300) to deionized water is 1.75:1000, and the pH value is adjusted to 6 with acetic acid or ammonia water.
[0083] Process: 1. Chemical decontamination of the surface of aluminum alloy workpieces (immerse the workpiece in an organic solution containing acetone and ethanol for 20 minutes).
[0084] 2. Ultrasonic cleaning for 60 minutes, let it stand, and heat and dry it.
[0085] 3.MAO: Immerse the workpiece in an electrolytic cell and perform constant current oxidation first: current density 1.0A / dm 2, duty cycle 30%, negative voltage 150 V, frequency 220 Hz, oxidation time 20 min; then constant voltage oxidation: voltage 250 V, duty cycle 20%, negative voltage 150 V, frequency 1100 Hz, oxidation time 15 min.
[0086] 4. Oxidation sealing: Heat the sealing liquid and keep it at 60°C, immerse the workpiece in the sealing liquid for 9 minutes.
[0087] 5. Drying: Dry the surface of the workpiece with hot air.
[0088] Table 1 Dissolution time (s) Example 1 325 Example 2 291 Example 3 343 Example 4 248 Example 5 264 Comparative Example 1 95 Comparative Example 2 71 No defect blank sample 185 It can be seen from Table 1 that the mass ratio of magnesium oxide and aluminum carbonate powder affects the film-forming and corrosion resistance effects. The increase in the mass ratio of the two has a convergent relationship on the improvement of corrosion resistance. Taking the lower limit of the surface reaction or eliminating the surface reaction affects the final film-forming effect.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for repairing aluminum alloy surface defects, characterized in that: include: Pretreatment: taking a surface-cleaned aluminum alloy and covering defects of the aluminum alloy with a composition, wherein the composition includes magnesium oxide powder and aluminum carbonate magnesium powder; Surface reaction, placing the aluminum alloy in a reaction chamber, introducing carbon dioxide into the reaction chamber, and forming a first film layer at defects of the aluminum alloy; curing, after the surface reaction is completed, continuing to introduce carbon dioxide into the reaction chamber to form a second film layer on the first film layer; After the curing step is completed, the aluminum alloy is cooled and the composition attached to the surface is removed.
2. The method for repairing aluminum alloy surface defects according to claim 1, characterized in that: The mass ratio of the magnesium oxide powder to the aluminum carbonate powder is 1:(1-3).
3. The method for repairing aluminum alloy surface defects according to claim 1, characterized in that: The magnesium oxide powder is nano magnesium oxide.
4. The method for repairing aluminum alloy surface defects according to claim 1, characterized in that: In the surface reaction step, the flow rate of carbon dioxide is 1L / h-3L / h, the temperature in the reaction chamber is 80°C-100°C, the surface pressure in the reaction chamber is 1Bar-1.5Bar, and the reaction time is 5h-10h.
5. The method for repairing aluminum alloy surface defects according to claim 1, characterized in that: During the curing step, the flow rate of carbon dioxide is less than 0.5 L / h, and the temperature in the reaction chamber is 70° C.-100° C.
6. The method for repairing aluminum alloy surface defects according to claim 1, characterized in that: During the curing step, the temperature fluctuation in the reaction chamber is less than 5°C / h.
7. The method for repairing aluminum alloy surface defects according to claim 1, characterized in that: In the surface reaction step, the temperature of the carbon dioxide introduced is 90°C-110°C; And / or, in the curing step, the temperature of the carbon dioxide introduced is 18°C-25°C; And / or, before the pretreatment step, the aluminum alloy is also cleaned, and the cleaning step includes: placing the aluminum alloy to be repaired in anhydrous acetone and performing a first ultrasonic treatment, immersion, a second ultrasonic treatment and drying in sequence; the first ultrasonic treatment time is 50min-70min, the ultrasonic frequency is 100KHz-130KHz, and the ultrasonic power density is 15W / L-20W / L; the immersion time is 30min-40min; and the second ultrasonic treatment time is 10min-20min.
8. An aluminum alloy, characterized in that: The method is repaired by any one of claims 1 to 7.
9. A rotor made of aluminum alloy, characterized in that: The method of any one of claims 1 to 7 is used for repair, wherein the total thickness of the first film layer and the second film layer is 5 μm to 10 μm.
Citation Information
Patent Citations
Carbon dioxide methanation catalyst as well as preparation method and application thereof
CN118002133A
